2013
DOI: 10.3109/00365521.2013.848468
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriinfection is associated with advanced colorectal neoplasia

Abstract: H. pylori infection is associated with the development of advanced colorectal neoplasia. More studies are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
1
16
2
Order By: Relevance
“…While the association between H. pylori infection and colorectal neoplasia has been suggested in some studies, others disagree . The reason for this discrepancy is currently uncertain, but our results suggest that age is an important factor that determines the association between H. pylori and ACN.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…While the association between H. pylori infection and colorectal neoplasia has been suggested in some studies, others disagree . The reason for this discrepancy is currently uncertain, but our results suggest that age is an important factor that determines the association between H. pylori and ACN.…”
Section: Discussioncontrasting
confidence: 59%
“…Unlike for CRA and CRC, the relationship between H. pylori infection and ACN has been reported in only a few studies. Shmuely et al reported on the relationship between H. pylori infection and ACN with odds ratios (OR) of 9.5 and 7.9 for ACN and CRC, respectively. However, the OR for CRC was unusually higher than that of previous meta‐analyses, and the number of cases in their study was relatively small (ACN, n = 77).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have reported on a positive association between H. pylori infection and increased risk for the development of colonic neoplasms [19][20][21][22][23][24]. This has led to the proposal of combining colorectal cancer screening with PGI, PGII, and G-17 assessment.…”
Section: The Influence Of Gastrointestinal Endoscopymentioning
confidence: 99%
“…Serology was utilized as the detection method for H. pylori in 14 studies[8, 9, 21, 23, 25-27, 31-35, 38, 39], pathology in 4[3,22,40,42], UBT in 4[6,37], CLO in 6[19,24,30,36], and combining UBT and CLO in 2[28,29]. Gender and age are reported in 22[3,6,8,9,19,[21][22][23][24][25][26][27][28][29][30][34][35][36][37][38][39][40] and 27[3,6,8,9,19,[21][22][23][24][25][26][27][28][29][30][31]…”
mentioning
confidence: 99%